Rancang Bangun Sistem E-Sertifikat Pada Lembaga Pelatihan Kerja Global Skill Mandiri Medan - suheri (Jurnal Nasional Teknologi Komputer, 2024)
In today's technological advances, certificates exist not only in physical printed form but also in the form of documents that can be accessed anytime and anywhere online. In every training activity carried out by LPK Global Skill Mandiri, it always provides certificates to its participants. By creating an e-certificate system, every participant who takes part in the training will receive an online certificate which can be downloaded on a website-based system. To produce a system that suits user needs, this system was designed using the Agile method. With the help of the CodeIgniter framework, which is a framework in the PHP programming language that applies the MVC (Model, View, Controller) model, as well as with data storage media using RDBMS MySQL.